Recovery of High Concentration Hexavallent Irradiated Uranium From Inorganic Fission Products - Jassim, S.A. (Ibn AL-Haitham Journal For Pure and Applied Sciences, 2016)
In this study , extraction of irradiated high concentration hexavallent uranium from fission products ( high gamma radiation ) was carried out using multistages countercurrent continuous technique (mixer setller) , employing this technique requires a designing flow sheet that recover all the amounts of uranium and to minimize its losses in the nuclear waste streams. Due to the several parameters required to reach this design, SEPHIS program which is one of the famous code in this field were used to select the optimum conditions through many theoretical runs , finally the experimental results give a good assurance in SEPHIS results and its optimum conditions.